Newborn Screening for Long-Chain 3-Hydroxyacyl-CoA Dehydrogenase and Mitochondrial Trifunctional Protein Deficiencies Using Acylcarnitines Measurement in Dried Blood Spots—A Systematic Review of Test Accuracy - Stinton, Chris; Fraser, Hannah; Geppert, Julia; Johnson, Rebecca; Connock, Martin; Johnson, Samantha; Clarke, Aileen; Taylor-Phillips, Sian (Frontiers in Pediatrics, 2021)
Background: Long chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) and mitochondrial trifunctional protein (MTP) deficiencies are rare autosomal recessive fatty acid β-oxidation disorders. Their clinical presentations are variable, and premature death is common. They are included in newborn blood spot screening programmes in many countries around the world. The current process of screening, through the measurement of acylcarnitines (a metabolic by-product) in dried blood spots with tandem mass spectrometry, is subject to uncertainty regarding test accuracy. Methods: We conducted a systematic review of literature published up to 19th June 2018. We included studies that investigated newborn screening for LCHAD or MTP deficiencies by tandem mass spectrometry of acylcarnitines in dried blood spots. The reference standards were urine organic acids, blood acylcarnitine profiles, enzyme analysis in cultured fibroblasts or lymphocytes, mutation analysis, or at least 10-year follow up. The outcomes of interest were sensitivity, specificity, PPV, and NPV. Assessment of titles, abstracts, and full text papers, and quality appraisal were carried out independently by two reviewers. One reviewer extracted study data. This was checked by a second reviewer. Results: Ten studies provided data on test accuracy. LCHAD or MTP deficiencies were identified in 23 babies. No cases of LCHAD/MTP deficiencies were identified in four studies. PPV ranged from 0% (zero true positives and 28 false positives from 276,565 babies screened) to 100% (13 true positives and zero false positives from 2,037,824 babies screened). Sensitivity, specificity, and negative predictive value could not be calculated as there was no systematic follow up of babies who screened negative. Conclusions: Test accuracy estimates of screening for LCHAD and MTP deficiencies with tandem mass spectrometry measurement of acylcarnitines in dried blood were variable in terms of positive predictive values. Screening methods (including markers and thresholds) varied between studies, and sensitivity, specificity, and negative predictive values are unknown.